2021
DOI: 10.1016/j.celrep.2021.109100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dynamic RNA-binding proteins uncovers a Cpeb4-controlled regulatory cascade during pathological cell growth of cardiomyocytes

Abstract: RNA-binding proteins (RBPs) control critical aspects of cardiomyocyte function, but the repertoire of active RBPs in cardiomyocytes during the growth response is largely unknown. We define RBPs in healthy and diseased cardiomyocytes at a system-wide level by RNA interactome capture. This identifies 67 cardiomyocyte-specific RBPs, including several contractile proteins. Furthermore, we identify the cytoplasmic polyadenylation element-binding protein 4 (Cpeb4) as a dynamic RBP, regulating cardiac growth both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…These findings support a direct connection between CPEB phase separation behavior and their activity within CCR4-NOT repressor complexes. Our observations are also in line with another recent study showing that CPEB4 acts as a repressor of transcription factor expression in the heart, acting both at the level of translation and mRNA decay [90].…”
Section: Discussionsupporting
confidence: 93%
“…These findings support a direct connection between CPEB phase separation behavior and their activity within CCR4-NOT repressor complexes. Our observations are also in line with another recent study showing that CPEB4 acts as a repressor of transcription factor expression in the heart, acting both at the level of translation and mRNA decay [90].…”
Section: Discussionsupporting
confidence: 93%
“…It was recently identified as a critical regulator of cardiomyocyte function (13). Depletion of CPEB4 led to pathological cellular growth both in vitro and in vivo in cardiomyocytes and decreased cardiac function (13). Taken together, we hypothesize a mechanism in which a genetic variant at the enhancer region of CPEB4 gene led to DNAm, which down-regulated the expression of the CPEB4 gene (for instance, by disrupting the binding of a transcription factor).…”
Section: Identifying Consistent Smr Associations Across Multi-omicsmentioning
confidence: 74%
“…Notably, in a recent work, Riechert et al reported CPEB4 as a key regulator of cardiac growth and function. CPEB4 knockdown increased the expression of NPPA-NPPB cluster (13), which are established risk markers for AF (22). Our results suggested CPEB4 as a potential drug target for AF prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, numerous monogenic diseases in the human population, including some heart diseases (see below), are caused by damaging mutations in RBP genes. 10 Using RNA interactome capture, 2 laboratories recently purified hundreds of RBPs from cultured or primary rodent cardiomyocytes, 11,12 many of which were cardiomyocytespecific, suggesting that they perform specialized functions in heart muscle. Among those identified were several RBPs with previously documented roles in cardiomyocytes, primarily as mediators of alternative splicing, which dictate the properties of target RNAs and the activities of encoded proteins based on exon composition.…”
mentioning
confidence: 99%